Предмет: Алгебра,
автор: vataevaa69kesa
Упростите выражения
4a*(a-2)-(a-4)^2=
2*(m+1)^2-4m=
Ответы
Автор ответа:
1
4a*(a-2)-(a-4)^2=2*(m+1)^2-4m
4a^2-8a-a^2+8a-16=2m^2+4m+2-4m
3a^2-16=2m^2+2
3a^2-2m^2-18=0
4a^2-8a-a^2+8a-16=2m^2+4m+2-4m
3a^2-16=2m^2+2
3a^2-2m^2-18=0
vataevaa69kesa:
4a*(a-2)-(a-4)^2=
Похожие вопросы
Предмет: Математика,
автор: bolatovatamiris
Предмет: Алгебра,
автор: dsadasdahssdkl
Предмет: Информатика,
автор: elizavetanuzda
Предмет: Геометрия,
автор: hhh92
Предмет: Биология,
автор: longlivebarbie